2007
DOI: 10.1002/ejic.200700021
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Control in the Protonation of [Cp*Mo(dppe)H3] by CF3COOH

Abstract: The outcome of the reaction between [Cp*Mo(dppe)H3] [dppe = 1,2‐bis(diphenylphosphanyl)ethane] and trifluoroacetic acid (TFA) is highly dependent on the solvent and the TFA/Mo ratio. The dihydride compound [Cp*Mo(dppe)H2(O2CCF3)] is obtained selectively when the reaction is carried out in aromatic hydrocarbons (benzene, toluene) when using less than one equivalent of TFA. The dihydride is also the end product when THF or MeCN are used as solvent, independent of the TFA/Mo ratio. In benzene/toluene the use of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 34 publications
2
21
1
Order By: Relevance
“…S11). It did not reveal a n NH band attributable to Et 3 NH þ , although the formation of ionic species is evident from the presence of the CF 3 COO À anion n as OCO band at 1673 cm À1 [45]. Hence, this experiment justifies the lack of observation of a spectroscopic signature for the ammonium ion of 4 in the IR spectrum.…”
Section: Reaction Between Trans-ptbr 2 (C 2 H 4 )(Hnet 2 ) and Hnet 2contrasting
confidence: 45%
“…S11). It did not reveal a n NH band attributable to Et 3 NH þ , although the formation of ionic species is evident from the presence of the CF 3 COO À anion n as OCO band at 1673 cm À1 [45]. Hence, this experiment justifies the lack of observation of a spectroscopic signature for the ammonium ion of 4 in the IR spectrum.…”
Section: Reaction Between Trans-ptbr 2 (C 2 H 4 )(Hnet 2 ) and Hnet 2contrasting
confidence: 45%
“…The investigation of hydrogen bonding and proton transfer to complex [Cp*WH 3 A C H T U N G T R E N N U N G (dppe)] followed a combined spectroscopic and theoretical protocol, similar to that used previously for complexes [Cp*MA C H T U N G T R E N N U N G (dppe)H] (M = Fe, Ru), [24,25,27] [Cp*MoA C H T U N G T R E N N U N G (dppe)H 3 ], [29,30] and [CpRuH(CO)A C H T U N G T R E N N U N G (PCy 3 )]. [34] Study of the starting trihydride complex: The synthesis and full characterization of this compound has been reported previously.…”
Section: Resultsmentioning
confidence: 99%
“…[24][25][26][27][28] Given the above scenario, it may be reasonable to expect that the kinetic preference for attack at an M-H site versus the metal lone pair should be greater for a polyhydride compound than for a monohydride compound. Recently, we reported detailed investigations [29,30] on the hydrogen bonding and proton transfer to complex [Cp*MoA C H T U N G T R E N N U N G (dppe)H 3 ], an electron-rich half-sandwich trihydride complex of Mo IV . [31] The protonation product observed by the use of either strong (HBF 4 , CF 3 COOH) or moderate (perfluoro-tert-butanol (PFTB), hexafluoroisopropanol (HFIP), p-nitrophenol) acids is the classical tetrahydrido derivative, [Cp*Mo-A C H T U N G T R E N N U N G (dppe)H 4 ] + , without detection of any nonclassical intermediate, even upon working at 200 K. On the other hand, use of even weaker proton donors (2,2,2-trifluoroethanol (TFE), 2fluoroethanol (MFE)), and low temperatures (200 K), backed up by a theoretical investigation, revealed that the most likely site of attack is a hydride ligand.…”
Section: Introductionmentioning
confidence: 99%
“…Dihydrogen bonded and ionpaired adducts are intermediates along the proton transfer path eventually producing a dihydrogen ligand that may evolve towards a dihydride through the cleavage of the H-H bond [33][34][35][36][37][38][39][40][41][42]. The effect of the metal centre and of the electronic properties of the ligands on the acidity of the dihydrogen ligand [46], and the effect of the solvent on the nature of the protonation product [47] have been investigated.…”
Section: The Ece Mechanism (1 Equiv Acid)mentioning
confidence: 99%